THE IMPACT OF THE COVID-19 PANDEMIC ON STUDENT RELIGIOSITY AT AHMAD DAHLAN UNIVERSITY YOGYAKARTA - Yusron Masduki; Mohd Fauzi Abu Hussin; Hanif Cahyo Adi Kistoro; Parjiman Parjiman; Ahmad Zainuri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The spread of Covid-19 has had a significant impact on education, especially in the field of religion. The purpose of this study was to see how the pandemic affected the efforts of Ahmad Dahlan University Yogyakarta to increase student religiosity. The participants in this study were eight students and university officials from Ahmad Dahlan University in Yogyakarta’s PAI Study Program. Purposive sampling was used as a technique for selecting study subjects. This study used an in-depth interview approach through an interview guide that had been made to collect data. Data analysis included stages such as grouping relevant themes or meanings from participant responses, describing textually and structurally, and fundamentally describing all important meanings into a complete picture of the phenomenological study findings experienced by participants. According to the findings, the Covid-19 pandemic had an effect on student religiosity. First, students’ religious spirit and motivation were diminished. Second, limited activities contribute to ennui among students. Third, the institution was working to develop policies and technological guidelines for the entire academic community’s activities. In addition, there was also optimization of social media for learning and strengthening religious activities through the campus’ official media channels.